Translation and implementation of evidence-based practice - Palinkas, Lawrence A.; Soydan, Haluk, 1946- (New York : Oxford University Press, 2011)
This book is about conducting research on the process and outcomes of the translation and implementation of evidence-based practices in social work. Its aims are to outline a strategy for conducting such research and to identify the infrastructure and resources necessary to support such research within the field of social work.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 18, 2012).
Includes bibliographical references and index.
Keywords: Evidence-based social work; Social service -- Practice; Social service -- Research